Efeito da solubilização na microestrutura e na resistência à corrosão de um aço inoxidável duplex - Cronemberger, Maria Eurenice Rocha (2013)
Corrosion is one of the most serious problems faced by the petrochemical industry, because the wear of machinery and equipment, resulting from the corrosion process, entails economic, operational and safety impacts. The combination of good mechanical properties and corrosion resistance of duplex stainless steels, especially in harsh environments, has been the main attraction for its increasing use in the petrochemical industry. This steel has a mixed structure of austenite and ferrite whose arrangement and distribution influence its properties. The formation of intermetallic phases during the heat treatment of this steel is a crucial point in its performance, may avoid the obtainment or lead to degradation of its properties. This study investigates the SAF 2205 duplex stainless steel as-cast and its microstructural evolution after solution annealing treatment under different conditions. The aim was to detect the effects on the microstructure and its influence both in hardness and corrosion resistance of the steel, with the variation of the solution aneealing duration and the way of cooling. The evaluation of the results was based on the microstructural analysis, energy dispersive spectrometry measurements, X-ray diffraction, hardness and electrochemical tests. It was observed that the solution annealing treatment affects the microstruture homogeneity, and the way of cooling promotes the intermetallic phases’ precipitation. The slow cooling, in furnace, induces the precipitation of intermetallic phases, sigma and '. The solution annealing during 240 minutes allowed obtaining a favorable ratio between ferrite and austenite phases, which improve the steel passivation process. Besides, the results showed that the increase of the solution annealing duration combined with a slower cooling, in furnace, increase the hardness and decrease significantly the corrosion resistance of steel due to the precipitation of the sigma and ’ phases.